Hepatitis B Surface Antigen Loss and Hepatocellular Carcinoma Development in Patients With Dual Hepatitis B and C Infection. Issue 10 (March 2016) - Yang, Wan-Ting; Wu, Li-Wei; Tseng, Tai-Chung; Chen, Chi-Ling; Yang, Hung-Chih; Su, Tung-Hung; Wang, Chia-Chi; Kuo, Stephanie Fang-Tzu; Liu, Chen-Hua; Chen, Pei-Jer; Chen, Ding-Shinn; Liu, Chun-Jen; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are 2 major causes of chronic viral hepatitis. It is still unclear how HCV coinfection affects HBV replication and clinical outcomes in HBV/HCV coinfected patients. We conducted a longitudinal study, which enrolled 111 patients with HBV/HCV coinfection and 111 propensity score-matched controls with HBV monoinfection. Both groups had comparable baseline age, sex, fibrosis stage, levels of HBV DNA, and HBV surface antigen (HBsAg). The HCV coinfection and other host/viral factors were correlated with various outcomes, including HBsAg loss and cirrhosis/hepatocellular carcinoma (HCC) development. After a 10-year follow-up, we found that HCV coinfection itself was not associated with HBsAg loss. However, coinfected patients with alanine aminotransferase (ALT) level >80 U/L had a higher chance of HBsAg loss than those with ALT level ≤80 U/L [hazard ratio (95% confidence interval): 4.41 (1.75–11.15)] or matched controls with HBV monoinfection [hazard ratio (95% confidence interval): 3.40 (1.54–7.50)]. Besides, both HCV coinfection and higher ALT levels were associated with higher HCC risks and the HCC risks remained even after HBsAg loss in HBV/HCV con-infected patient. HCV coinfection is not associated with HBsAg loss. A higher ALT level is a major determinant of HBsAg loss in patients with HBV/HCV coinfection. Both HCV coinfection and a higher ALT level were independent risk factors of HCC.